PENGARUH LEADER MEMBER EXCHANGE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR: PERAN MEDIASI WORK ENGAGEMENT - Marchyta, Nony Kezia; Lomban, Anastasia Angelina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024DO - 10.24843/EEB.2024.v13.i05.p18, 2024)
Despite the economic slowdown due to the Covid-19 pandemic, PT.X, which operates in the automotive sector, still recorded positive growth during 2021. The leadership of PT.X stated that one of the supporting factors is the high consistency in leadership and human resources. However, the wider the coverage area of PT.X, the more it emphasizes the importance of quality relationships between leaders and subordinates. This study aims to test the influence of leader-member exchange on organizational citizenship behavior with work engagement as a mediating variable at PT.X's employees. This study was quantitative research with purposive sampling. The seventy respondents were permanent employees who had worked at PT. X for at least one year. The results showed that leader-member exchange had a positive effect on organizational citizenship behavior, the leader-member exchange had a positive impact on work engagement, work engagement had a positive effect on organizational citizenship behavior, and work engagement mediated the influence of leader-member exchange towards organizational citizenship behavior. Employees with a good relationship with the leader tend to have high work satisfaction and productivity and are willing to work more than necessary for the company's growth. An increase in employees' understanding that their work is essential and purposeful can increase in organizational citizenship behavior. Therefore, leader-member exchange and work engagement will improve the company's organizational citizenship behavior.